2007
DOI: 10.1002/pros.20553
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐6 undergoes transition from growth inhibitor associated with neuroendocrine differentiation to stimulator accompanied by androgen receptor activation during LNCaP prostate cancer cell progression

Abstract: These studies suggest that acquisition of endogenous IL-6 production after prolong exposure of prostate cancer cells to IL-6 may contribute to an autocrine cell growth stimulation. Furthermore, the transition of IL-6 from a paracrine growth inhibitor to an autocrine growth stimulator suggests that IL-6 plays an important role during prostate cancer progression, possibly androgen-independent progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
90
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(93 citation statements)
references
References 33 publications
2
90
0
1
Order By: Relevance
“…24 In in vitro experiments, IL-6 has been reported to affect cell proliferation and to induce neuroendocrine (NE) differentiation [25][26][27][28] of prostate cancer cells in a complicated manner depending on autocrine or paracrine cytokine action. [27][28][29] IL-6 binds to its receptor and mainly transduces signals through MAP kinase/ ERK, PI3K/AKT and STAT3 pathways. 30 It has been shown in oligodendrocytes from the motheaten mice, which have a genetic defect in the SHP-1 gene, that SHP-1 expression controls the activation of STAT3 by IL-6 signaling.…”
mentioning
confidence: 99%
“…24 In in vitro experiments, IL-6 has been reported to affect cell proliferation and to induce neuroendocrine (NE) differentiation [25][26][27][28] of prostate cancer cells in a complicated manner depending on autocrine or paracrine cytokine action. [27][28][29] IL-6 binds to its receptor and mainly transduces signals through MAP kinase/ ERK, PI3K/AKT and STAT3 pathways. 30 It has been shown in oligodendrocytes from the motheaten mice, which have a genetic defect in the SHP-1 gene, that SHP-1 expression controls the activation of STAT3 by IL-6 signaling.…”
mentioning
confidence: 99%
“…This enhanced sensitivity of LNCaP/IL-6#1 to androgen withdrawal was more remarkable in vivo; that is, after castration, LNCaP/IL-6#1 tumour rapidly regressed and completely disappeared. According to previously reported studies, the effects of IL-6 on the growth of LNCaP cells seem to be puzzling with some groups showing growth stimulation, whereas others showing growth inhibition Lee et al, 2003Lee et al, , 2007Jia et al, 2004). For example, Lee et al (2007) reported the bifunctional action of IL-6 according to the manner of its secretion; that is, IL-6 acts as a growth inhibitor for LNCaP cells by a paracrine mechanism, whereas endogenously produced IL-6 stimulates LNCaP cell growth by an autocrine mechanism.…”
Section: Discussionmentioning
confidence: 98%
“…According to previously reported studies, the effects of IL-6 on the growth of LNCaP cells seem to be puzzling with some groups showing growth stimulation, whereas others showing growth inhibition Lee et al, 2003Lee et al, , 2007Jia et al, 2004). For example, Lee et al (2007) reported the bifunctional action of IL-6 according to the manner of its secretion; that is, IL-6 acts as a growth inhibitor for LNCaP cells by a paracrine mechanism, whereas endogenously produced IL-6 stimulates LNCaP cell growth by an autocrine mechanism. As most of the previously observed effects of IL-6 on the growth of prostate cancer cells were examined in vitro, this study is the first to demonstrate the following evidence that overexpression of IL-6 in LNCaP cells enhanced their sensitivity to androgen withdrawal both in vitro and in vivo, resulting in marked growth inhibition immediately after androgen ablation.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations